Exploration of visual image design in sports colleges and Universities. Taking the visual image design of Wuhan Sports Institute as an example - Wang, Wenyu; Lv, Jinlong; Dai, Zhengqing (Technium Social Sciences Journal, 2020)
The university visual identification system is an extension of the enterprise visual image identification system, which displays the university visual brand image jointly through the logo, standard color, standard font, auxiliary graphics and standard combination. As far as the visual image recognition system of sports colleges and universities is concerned, the refinement, digitization and standardization of the image are important means to realize the visual symbol of sports characteristics and its attached value and cultural connotation. This article from the perspective of visual communication design, following the integration and fine-tuning and complement, using the theory of the method of literature study method, graphic method and contrast method, etc, has carried on the induction summary to the visual image of sports colleges and universities at home and abroad, taking Wuhan sports college as an example, discusses the basic connotation of Visual identification system, Wuhan institute of physical education including signs, standard colors, fonts, graphics and standards, etc., and the design result is given.